2022
DOI: 10.1021/acs.est.2c05537
|View full text |Cite
|
Sign up to set email alerts
|

Triclosan Promotes Conjugative Transfer of Antibiotic Resistance Genes to Opportunistic Pathogens in Environmental Microbiome

Abstract: Although triclosan, as a widely used antiseptic chemical, is known to promote the transmission of antibiotic resistance to diverse hosts in pure culture, it is still unclear whether and how triclosan could affect the transmission of broad-host-range plasmids among complex microbial communities. Here, bacterial culturing, fluorescence-based cell sorting, and high-throughput 16S rRNA gene amplicon sequencing were combined to investigate contributions of triclosan on the transfer rate and range of an IncP-type pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 55 publications
0
14
0
1
Order By: Relevance
“…coli HB101) on the selection plates to exclude spontaneous mutation to produce false transconjugants. For the wastewater microbiota conjugation system, flow cytometric cell detection (CytoFLEX,Beckman Coulter, USA) was performed to quantify the number of transconjugants based on the number of green fluorescent cells . The excitation and emission wavelengths were set as: 561-614/42 ( dsRed ), and 488-525/40 ( gfp ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…coli HB101) on the selection plates to exclude spontaneous mutation to produce false transconjugants. For the wastewater microbiota conjugation system, flow cytometric cell detection (CytoFLEX,Beckman Coulter, USA) was performed to quantify the number of transconjugants based on the number of green fluorescent cells . The excitation and emission wavelengths were set as: 561-614/42 ( dsRed ), and 488-525/40 ( gfp ).…”
Section: Methodsmentioning
confidence: 99%
“…For the wastewater microbiota conjugation system, flow cytometric cell detection (CytoFLEX,Beckman Coulter, USA) was performed to quantify the number of transconjugants based on the number of green fluorescent cells. 29 The excitation and emission wavelengths were set as: 561-614/42 (dsRed), and 488-525/40 (gf p). To identify the community structure of transconjugants in wastewater microbiota, the transconjugants were subjected to fluorescence-activated cell sorting (FACS) (BD FACS Aria III, USA).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…For example, the plastic additive triclosan can cause aquatoxicity and promote the conjugative ARGs transfer to opportunistic pathogens in activated sludge microbiome. Therefore, chemicals released from microplastics pose a realistic threat to One Health by accelerating ARGs spreading . For example, the marine environments contaminated by a mixture of MPs and chemical additives have been demonstrated to coselect antibiotic resistance in bacterial pathogens and transmit it to humans through seafood .…”
Section: Microplastics Adsorbed and Released Chemicals Enhance Args T...mentioning
confidence: 99%
“…Therefore, chemicals released from microplastics pose a realistic threat to One Health by accelerating ARGs spreading. 18 For example, the marine environments contaminated by a mixture of MPs and chemical additives have been demonstrated to coselect antibiotic resistance in bacterial pathogens and transmit it to humans through seafood. 4 However, the detailed impacts of these plastic chemical additives and the underlying biological mechanisms underpinning the accelerated ARGs spreading remain ambiguous.…”
Section: Chemicals Enhance Args Transmissionmentioning
confidence: 99%
“…Triclosan (5-chloro-2-(2′,4′-dichlorophenoxy) phenol; TCS), a type of broad-spectrum antimicrobial and PPCP, has been widely distributed in the aquatic environment, especially since the coronavirus disease 2019 (COVID-19) pandemic [30]. Compared to antibiotics, non-antibiotic antiseptic products are not subject to prescription, and their consumption has surged during the COVID-19 pandemic with the raising global awareness of sanitation, which could threaten public and environmental health by promoting the propagation of antimicrobial resistance [31,32]. Previous studies have demonstrated that TCS at environmentally relevant concentrations can stimulate the horizontal gene transfer (HGT) of antibiotic-resistance genes (ARGs) [33][34][35].…”
Section: Introductionmentioning
confidence: 99%